ЧТО ЖЕ ТЫ ПЛАЧЕШЬ: KAJ PA JOKAŠ? JUXTAPOSITION OF RUSSIAN AND SLOVENIAN STRUCTURE WITH PARTICLES FROM THE PERSPECTIVE OF CONSTRUCTION GRAMMAR (Philological Studies, 2024)
This article juxtaposes the Russian structure ЧТО ЖЕ + NP – Nom + VP with the Slovene structure KAJ PA + (NP – Nom) + VP with the help of the theoretic principles of Construction Grammar. Firstly, the article tries to prove that both of the above-mentioned constructions have all of the properties which are requested by the Construction Grammar for defining a multi-word expression as the concept construction; and secondly, it tries to expose the dependency of meanings and functions of particles to the other elements in the construction and to the whole construction.